Report of the Scientific Field Survey on Lake Hovsgol and its Tributaries - Sigiyama, M; Dulmaa, A; Drucker, VV (Proceedings of the Mongolian Academy of Sciences, 2011)
The present report gives an intermediate account of a collaborative research work at the Lake Hovsgol. The fi eld survey took place from 9 August – 16 August, 2009 and covered sampling stations as follows, 15 stations at the Lake Hovsgol, 1 station on the Khar Us River, 1 station on the Egiin Gol River. DOI: http://dx.doi.org/10.5564/pmas.v0i4.53 Proceedings of the Mongolian Academy of Sciences 2009 No.4 pp.101-102